2013
DOI: 10.1111/j.2047-2927.2013.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of testosterone to the clock system in rat prostate mesenchyme cells

Abstract: SUMMARYCircadian rhythms are modulated in a variety of peripheral tissues including the prostate, in which the mesenchyme and epithelium cells are controlled under androgens. Here, we investigated the testosterone regulation of core clock genes such as Bmal1, Clock, Per2 and Nr1d1 under a deficient state of testosterone. In vivo studies showed that the Bmal1 mRNA expression in the prostates displayed a peak at ZT 20 and a trough at ZT 12. Both Bmal1 and Clock transcripts decreased after castration. Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…This shift in Per2 levels was coincident with testosterone synthesis, suggesting strong association between androgen production and the expression of Per2. Additional reports showed that Bmal1 and Clock, but not Per2 and Nr1d1/Rev–ErbAα, are down-regulated by testosterone deficiency (Kawamura, et al 2014). Thus, it is likely that Per2 that drives testosterone levels.…”
Section: Relation Between the Circadian Clock And Androgensmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift in Per2 levels was coincident with testosterone synthesis, suggesting strong association between androgen production and the expression of Per2. Additional reports showed that Bmal1 and Clock, but not Per2 and Nr1d1/Rev–ErbAα, are down-regulated by testosterone deficiency (Kawamura, et al 2014). Thus, it is likely that Per2 that drives testosterone levels.…”
Section: Relation Between the Circadian Clock And Androgensmentioning
confidence: 99%
“…Both male and female Bmal1 knockout (K/O) mice are infertile (Alvarez, et al 2008). Male Bmal1 K/O mice had low testosterone and high luteinizing hormone serum concentrations, suggesting a role for Bmal1 in androgen production, while in turn, Bmal1 and Clock are down-regulated by testosterone deficiency (Kawamura et al 2014). Importantly, Leydig cells, which produce testosterone, rhythmically express Bmal1 protein (Alvarez et al 2008).…”
Section: Relation Between the Circadian Clock And Androgensmentioning
confidence: 99%
“…Transcription factors mediating circadian rhythms are found in all cells and can function autonomously [25]. There is evidence for a number of different mechanisms coordinating the master clocks [26] within the suprachiasmatic nucleus (SCN) with peripheral cycling [8][9][10][25][26][27][28][29][30]. During neonatal development, the phase relationship of the circadian clock gene Per2 expression within the SCN and peripheral tissues can shift suggesting entrainment to organ-specific time cues at different developmental stages [27].…”
Section: Introductionmentioning
confidence: 99%
“…liver, oviduct) are unknown. Further, the threshold for the effects of androgens on clock gene expression have not been established, though some evidence suggests a potent effect in the nanomolar range [47,48]. We have attempted to determine if androgen can affect the timing of PER2::LUC expression at a level several fold higher than that found in serum from women with PCOS.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism whereby excess androgen can alter the timing of the clock remains to be determined, though it is likely due to a direct influence of ligand bound androgen receptor on clock gene expression [47,48]. To address this hypothesis we treated tissue explant cultures of liver, lung, pituitary, ovarian follicles, oviduct, WAT and SCN from adult female PER2::LUC mice (congenic on C57BL6/j) with several concentrations of DHT (100nM-1μM).…”
Section: Gestational Androgen Excess Differentially Affects Per2::lucmentioning
confidence: 99%